EDUCATIONAL QUALITY MANAGEMENT IN HIGHER EDUCATION INSTITUTIONS - Sodiq Usmonov Usmonovich; Alimova Kunduz Oybek qizi (International Journal of Innovations in Engineering Research and Technology, 2021)
he article reflects on the problems associated with definition of the important approaches to a quality development of management system for higher educational establishments.